Infection of commercial laying hens with Salmonella Gallinarum: clinical, anatomopathological and haematological studies - Freitas Neto, OC; Arroyave, W; Alessi, AC [UNESP]; Fagliari, JJ [UNESP]; Berchieri, A [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2007)
This study aimed at evaluating the susceptibility of commercial laying hens to Salmonella Gallinarum (SG). Two experiments were carried using a mutant strain of Salmonella Gallinarum resistant to nalidix acid (SGNALr). In the first trial, the resistance of birds was evaluated based on clinical signs, faecal shedding, and mortality. It was carried out with six lines of commercial layers being three light white layers, considered to be resistant to SG (W1, W2, W3), and three semi-heavy brown varieties (B1, B2, B3), considered susceptible to SG. Each group contained 15 one-day-old birds. Hens were inoculated in the crop at 5 days of age with 0.2 mL of SGNALr neat culture. In addition, to each brown variety, a new group of 15 birds was challenged with 0.2mL of the same SGNALr culture diluted at 10-3. At the end of the first experiment, the surviving birds were sacrificed, and microbiological culture of liver and spleen was performed. In the second experiment, white and brown birds were inoculated with neat culture at five days of age. Samples were collected for evaluation of blood parameters and histopathology assessment at 1, 3, 5, 7, 9, 12, and 14 days post-infection. The results of the first experiment showed higher resistance of white birds (p<0.05), although there was no uniformity in the responses against fowl typhoid among the birds within these groups. In the second experiment, there were differences between white and brown birds both in blood parameters and in organ lesion intensity.
Keywords: Fowl typhoid; Hematology; Laying hens; Salmonella Gallinarum; susceptibility